DETERMINATION OF OPTIMAL ALGAE CONCENTRATION FOR CONTINUOUS GROWTH OF Scenedesmus sp. IN CHU AND MODIFIED CHU MEDIA - Santos, K. R.; Mariano, A. B. (Revista de Engenharia Térmica, 2014)
The high cost of production in the cultivation of microalgae in photobioreactors is a barrier to be overcome, therefore is necessary to search to reduce the cost of cultivation. The objectives of this work are to compare the growth of the microalgae Scenedesmus sp. being cultivated in CHU medium and in an alternative medium composed mainly of fertilizer and to establish guidelines for growth under continuous mode. The research approach consisted on growing the microalgae in Erlenmeyer type photobioreactors and producing the growth curves for both media. The comparisons between the two, were made based upon three parameters: dry biomass, absorbance, and total lipid quantity. The experiments were made in triplicates in order to quantify the uncertainty in the measurements. The comparison of the cultivation in both media suggest that the modification of the chemical nutrients by fertilizer did not produce significant changes in the number of cells, dry biomass and lipids. In spite of that, the modification resulted in 20% cost reduction in the growth medium. In this way, the substitution of conventional nutrients by fertilizers, constitute an interesting alternative for the production of biomass from microalgae leading to a cost reduction. The results are used to develop strategies for continuous growth.